Galectin-1 as an Emerging Mediator of Cardiovascular Inflammation: Mechanisms and Therapeutic Opportunities - Seropian, Ignacio M.; González, Germán E.; Maller, Sebastián M.; Berrocal, Daniel H.; Abbate, Antonio; Rabinovich, Gabriel A. (Mediators of Inflammation, 2018)
Galectin-1 (Gal-1), an evolutionarily conserved β-galactoside-binding lectin, controls immune cell homeostasis and tempers acute and chronic inflammation by blunting proinflammatory cytokine synthesis, engaging T-cell apoptotic programs, promoting expansion of T regulatory (Treg) cells, and deactivating antigen-presenting cells. In addition, this lectin promotes angiogenesis by co-opting the vascular endothelial growth factor receptor (VEGFR) 2 signaling pathway. Since a coordinated network of immunomodulatory and proangiogenic mediators controls cardiac homeostasis, this lectin has been proposed to play a key hierarchical role in cardiac pathophysiology via glycan-dependent regulation of inflammatory responses. Here, we discuss the emerging roles of Gal-1 in cardiovascular diseases including acute myocardial infarction, heart failure, Chagas cardiomyopathy, pulmonary hypertension, and ischemic stroke, highlighting underlying anti-inflammatory mechanisms and therapeutic opportunities. Whereas Gal-1 administration emerges as a potential novel treatment option in acute myocardial infarction and ischemic stroke, Gal-1 blockade may contribute to attenuate pulmonary arterial hypertension.